(untitled) (Research, Society and Development, 2021)
Theoretical framework: Vegetable oils in the cosmetics market are gaining more and more notoriety because they contain mainly antioxidants as bioactive substances. Free radicals are one of the main responsible for skin aging, which is characterized by the set of inevitable changes that occur progressively in our body and is classified as intrinsic and extrinsic aging, leading to visual changes in both the epidermis and dermis due to the decrease in fibers collagen, elastic and glycosaminoglycans. Although it is currently impossible to prevent or reverse genetic processes of intrinsic aging, the changes caused by free radicals that trigger extrinsic aging can be prevented naturally with the use of oil-based cosmeceuticals. Objective: To review studies in the literature on the use of vegetable oils to prevent skin aging. Material and Methods: A qualitative review of the narrative-type literature was carried out, consulting scientific articles indexed in the electronic databases, SCIENCE DIRECT, SciELO, LILACS, MedLine and PubMed. Results: A current trend in the market for increasingly safer, biocompatible and effective cosmetics is to combine vegetable oils with antioxidant characteristics with other natural and / or synthetic actives in order to provide different functions and associated effects, such as combating premature aging and provide elasticity, firmness, hydration, among other benefits. Conclusion: Brazil has become a primordial country due to the abundance of natural resources in its forest, offering plant ingredients made up of bioactive compounds to the world scenario that work to combat the damage caused by free radicals.